Pesticides in the Semiarid of Alagoas: chemically dependent agriculture and its contradictions / Agrotóxicos no Semiárido de Alagoas: agricultura químicodependente e suas contradições - Lucas Gama Lima; Anderson Ribeiro Miranda; Érica Franciele da Silva Lima; José Rodolfo da Silva Santos; Jefferson Araújo Nascimento (Universidade Estadual de Alagoas, 2019)
Pesticides integrate the chemically dependent prevailing model in brazilian agriculture, and it is part of the complex capitalist totality in which agrochemical mega-corporations enjoy enormous centrality. The following lines have as objective to analyse the contradictions underlying dependent agriculture of pesticide in the Semiarid of Alagoas, providing a reflective input from data and information of outstanding relevance. The phenomenon of pesticides materializes in an unequal manner in the Semiarid of Alagoas and has resulted in acute socioenvironmental contradictions. The research was able to identify a significant incidence of human intoxication and risks of water and soil contamination with the chemical ingredients used in the plantations. In addition, it was found the subjection of income from peasant land to the capital by means of the regular purchase/sale of various pesticides. In the text are transmitted primary and secondary data collected throughout the investigation, through field visits to some of the communities situated on the banks of the Sertão Channel and the Moxotó river, Mesoregion of Sertão, western portion of the Semiarid, and collected through consultations with several state agencies